THE CHEMISTRY OF NUTRACEUTICALS: DRIVING HEALTH INNOVATIONS AND SHAPING NEW PARADIGMS (European Journal of Histochemistry)
Longevity is a complex biological process influenced by genetic, environmental, and lifestyle factors. The whole organism undergoes this process, with all the organs proceeding with specific biological clocks1. Recent evidence demonstrates the ability of several secondary metabolites, such as polyphenols, to inhibit molecular processes underlying aging events, acting on a wild array of biological targets belonging to several molecular networks. In addition, these compounds are associated with a reduced incidence of age-related diseases, including cardiovascular, neurodegenerative, and metabolic disorders. Mechanistic studies have elucidated how these molecules modulate oxidative stress, inflammation, and cellular senescence pathways, contributing to healthy aging2,3. In this context, the amounts of dietary phytochemicals associated with a decreased incidence of neurodegenerative and cardiovascular pathologies gain high doses that are difficult to obtain with a normal Western diet. In the recent literature, the term “superfood” has frequently been used, meaning dietary matrices, rich in compounds able to exert a plethora of biological effects resulting in a decrease of specific parameters, such as cholesterol levels, glycemia, oxidative stress and low-grade inflammation. The mentioned activities seem to be due to the whole food constituents, however in some cases it was possible to ascribe to specific compounds the salutogenic properties, as reported for beta-glucans or hydroxytyrosol. Also, functional foods may be part of salutogenic and preventive strategies. Indeed, as matrices enriched with compounds endowed with biological effects, they may act in a clinical space before drugs, beyond foods, with the aim of delaying molecular events linked to aging and inflammatory conditions.